Creutzfeldt–Jakob disease in pregnancy: the use of modified RT-QuIC to determine infectivity in placental tissues. Issue 1 (1st January 2021) - Luk, Collin C.; Mathiason, Candace K.; Orrù, Christina D.; Jansen, Gerard H.; Thiele, Allison; Caughey, Byron; Sim, Valerie L.
ABSTRACT: Sporadic Creutzfeldt–Jakob Disease (sCJD) rarely affects women of childbearing age. There is currently no evidence of vertical transmission. Given the biosafety implications of performing Caesarean sections (C-section) in these patients, we used sensitive real-time quaking-induced conversion (RT-QuIC) assays to test for the infectious prion protein (PrP Sc ) in products of gestation. A 35-year-old woman with sCJD presented in her 10 th gestational week with an eight month history of progressive cognitive impairment. During C-section, amniotic fluid, cord blood and placental tissue were collected and analysed using RT-QuIC protocols adapted for use with these tissues. The patient's diagnosis of sCJD, MM2 subtype, was confirmed at autopsy. There were borderline positive results in one sampled area of the placenta, but otherwise the cord blood and amniotic fluid were negative on our RT-QuIC assays. A healthy baby was delivered via C-section at 36 weeks and 3 days gestational age, with no evidence of neurological disease to date. We conclude that precautions should be taken with products of gestation, but the level of PrP Sc is extremely low.